Leaves of three, let them be: if it were only that easy!...this article originally appeared in Pediatric Nursing, 30(2), 129-135, and is reprinted with permission from the publisher - Allen PLJ (Dermatology Nursing, 2006)
Humans of all races and skin color are susceptible and uniquely sensitive to poison ivy, oak, and sumac. Contact with the plant oil, urushiol, found not only in the leaves but in the stems and roots, results in an allergic contact dermatitis in 50% to 60% of people. Clinical manifestations, differential diagnosis, complications, and treatments are discussed, with a special emphasis on the pediatric population.